Realisation Mechanisms for the Public Interest in Successful Urban Development Plans, with An Emphasis on Planning Theories of the Second Half of the 20th Century - Hossein Tarhani; Parvin Partovi (صفه)
What is known today as urban planning is perhaps conceived at a time when urban growth and its associated issues had reached the point of endangering the public interest with an unfair distribution of resources. This situation prompted urban planners to intervene in order to mitigate the conditions, bringing about a relatively balanced status into the need-resource dialectics. public interest is a recurring underlying issue for planning, and hence the need for further investigations.The current research is an attempt to explain realisation mechanisms for the public interest. The adopted approach is qualitative, with document-based methods used for data collection. Examples of the urban revitalisation plan for Medellín city in Columbia, the regeneration of Regent Park district in Toronto, the Zuidas Vision Plan, and the strategic development plan for Sydney—all internationally supported and evidently successful—are studied and analysed. Combining planning theories and content analysis of successful urban development plans, the research results in a public interest realisation mechanism diagram rendering them as processes. The main criteria for this diagram are fair distribution of resources, attention to environmental issues, social inclusion, housing, employment, interests-seeking, power networks, social communications and interactions, prompting social activism, Consciousness, and ethical commitments, norms and values; all illustrated in a network of relations in order to help planners ad planning processes realise the public interest.